The Role of Sauropus androgynus (L.) Merr. Leaf Powder in the Broiler Chickens Fed a Diet Naturally Contaminated with Aflatoxin - Yos Adi Prakoso; Puspitasari; Chylen Setiyo Rini; Andika Aliviameita; Siti Isrina Oktavia Salasia; Kurniasih; Ahmad Fadhli Dzil Ikram; Baristha Walalangi; Kukuh Priya Utama; Muhammad Fajar Al Huda; Neneng Ayu Su’udiyah (Journal of Toxicology)
Aflatoxin (AF) is the secondary metabolite of Aspergillus flavus and commonly contaminates feed during storage. AF causes lowered growth rate, stress, and increased mortality in the poultry, especially for broiler industries. The aims of this study are to determine the effects of Sauropus androgynus (L.) Merr. leaf powder (SAP) in the chickens fed a diet naturally contaminated with AF. A total of 108 chickens are divided into 6 group: group I fed with basal diet (AF not detectable); group II fed with basal diet (AF not detectable) + 5% SAP; group III with AF (>1 ppb <50 ppb); group IV with AF (>1 ppb <50 ppb) + 5% SAP; group V with AF (>51 ppb <100 ppb) + 5% SAP; group VI with AF (>101 ppb <150 ppb) + 5% SAP. The data of the body weight, feed intake and efficiency, the relative weight of liver, kidney, spleen, bursa of Fabricius (BF), histopathology, haematological profile, haemagglutination inhibition (HI) titer, AF residue, and immunohistochemistry are collected on days 7, 14, and 21. All the data were analysed using SPSS 16. The supplementation of 5% SAP in the chickens fed a diet naturally contaminated with AF showed the potential effects of the body weight performance, haematological profile protection, increase in the cellular and humoral immune responses, reduction of AF residue in the organ, protection of liver, kidney, spleen, and BF histopathology, and increase in the immune-expression of CD4+/CD8+ lymphocytes ratio (P < 0.05). It shows that 5% SAP can be used as the alternative herbal supplementation to depress the impacts of aflatoxicosis in the broiler chickens.